5‐Lipoxygenase mRNA and Protein Isoforms. (10th September 2013) - Ochs, Meike J.; Suess, Beatrix; Steinhilber, Dieter
Abstract 5‐Lipoxygenase (5‐LO) catalyses the two initial steps in the biosynthesis of leukotrienes, a group of inflammatory lipid mediators derived from arachidonic acid. An increased level of leukotrienes is associated with chronic inflammatory diseases such as asthma or atherosclerosis. In this MiniReview, we focus on recent findings regarding alternative splice variants of 5‐LO with a special emphasis on two potential protein isoforms expressed in human B‐lymphocytes which might be of interest as new drug targets.